2020
DOI: 10.3390/foods9080993
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-cysteine, Boswellia serrata, and Whey Protein on the Antioxidant and Physicochemical Properties of Pork Patties

Abstract: This study investigated the effects of L-cysteine (C) combined with Boswellia serrata (B) and whey protein (W) on the antioxidant and physicochemical properties of pork patties. Proximate composition, water holding capacity (WHC), pH, texture profile analysis, sensory evaluation, thiobarbituric acid-reactive substances (TBARS), DPPH radical-scavenging activity, volatile basic nitrogen (VBN), and color stability were assessed. Patty VBN gradually increased throughout the storage period. However, VBN for the C t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Yang et al . (2020) have also reported that VBN values of patties added with 0.25% cysteine powder were lower than control and those of added with whey. Cysteine could inhibit the deterioration of protein; however, whey powder could accelerate additional nitrogen.…”
Section: Resultsmentioning
confidence: 90%
“…Yang et al . (2020) have also reported that VBN values of patties added with 0.25% cysteine powder were lower than control and those of added with whey. Cysteine could inhibit the deterioration of protein; however, whey powder could accelerate additional nitrogen.…”
Section: Resultsmentioning
confidence: 90%
“…The L * values of experimental groups were higher than those of C3 or not significantly different, and a * values of experimental groups were lower than those of C3. It has been reported that L * value is increased whereas a * value is decreased when whey protein and ginseng powder are added to pork patties and sausages [44,45]. Increasing b * value of experimental groups might be because ginseng powder displayed a distinctive yellow color [45].…”
Section: Discussionmentioning
confidence: 96%
“…These results indicate that goat milk protein and ginseng powder can replace sodium triphosphate and ascorbic acid in terms in VBN. The study result of Yang [44] showed that TBARS and VBN values of pork patties added with 2% whey protein were significantly increased compared to control without addition. It is thought that containing 0.2 or 0.4% goat milk protein does not cause lipid or protein oxidation compared to adding 2%.…”
Section: Storage Characteristicsmentioning
confidence: 96%
“…The content of amino acids in meat was closely associated with the nutritional value [56] of meat protein and meat flavor [57]. The content of essential amino acids determined the quality of the protein, while flavor amino acids contributed to the taste.…”
Section: Discussionmentioning
confidence: 99%